THE ROLE OF SIMULATION TRAINING IN TEACHING HIGH-QUALITY CARDIOPULMONARY RESUSCITATION TO MEDICAL STUDENTS - Parpibaeva D. A.; Ergashov N. Sh.; Salaeva M. S.; Salimova N. D.; Boltaboev X.Q.; Turbanova U.V. (Journals Park Publishing, 2023)
Most medical schools teach cardiopulmonary resuscitation (CPR) to prepare students for first aid in clinical emergencies. Little is known about the optimal way to teach this important skill. Standard mannequins were used to practice practical skill and increase knowledge. In this study, we evaluated the comparative effectiveness of high-fidelity simulation training and standard mannequin training to teach quality CPR instructions to students of the Tashkent Medical Academy as outlined in the International Clinical Guidelines.